Mari Pakai Masker Putus Penyebaran COVID-19 - Rani Lisa Indra; Bayu Saputra; Erna Marni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
COVID-19 is a disease that attacks the respiratory system from no symptoms to death. Because more and more individuals are infected with COVID-19 who are asymptomatic, wearing a mask is one of the ways to prevent it. The purpose of this community service activity is to break the chain of the spread of COVID-19 and increase public awareness to always use masks when leaving the house. The target of this activity is the traders who sell at the Pekanbaru Dupa Market. The method of implementing this activity is in the form of social service by distributing cloth masks for free and providing information about the use of cloth masks with the target of changing the behavior of traders by always wearing masks when selling. The output of this service activity is publication in a community service journal. The result of this activity was the distribution of 100 cloth masks for free to traders. However, when the evaluation was carried out a week later, it turned out that there were still many traders who did not wear masks when selling. It is hoped that traders will increase awareness of wearing masks as a way to prevent transmission of COVID-19.